A CRITICAL PERSPECTIVE ON POLITICAL COMMUNICATION MANAGEMENT IN INDONESIAN DEMOCRACY IN THE 2024 PRESIDENTIAL ELECTION - Muhamad Agung Dharmajaya (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2026)
Political communication is an important element in the democratic process, especially in the Presidential Election (Pilpres). However, political communication practices in Indonesia are often characterized by various problems. This research aims to analyze the political communication management used by presidential candidates and their campaign teams in the 2024 presidential election. This research uses qualitative research methods. The data collection technique in this research is literature study. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The research results show that in the 2024 presidential election, presidential candidates and their campaign teams used various political communication management strategies to influence public opinion and win the election. They utilize mass media, social media, and campaign events with voters to spread campaign messages and build a positive image. Personal branding techniques and story narratives are used to create emotional closeness with voters and strengthen the candidate's political identity. In addition, candidates also use influencers and influential supporters to increase the candidate's visibility and popularity. All these efforts are designed to win public support and ensure victory in the presidential election.